2021
DOI: 10.1016/j.celrep.2021.108749
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-associated exportin-6 upregulation inhibits the transcriptionally repressive and anticancer effects of nuclear profilin-1

Abstract: SUMMARY Aberrant expression of nuclear transporters and deregulated subcellular localization of their cargo proteins are emerging as drivers and therapeutic targets of cancer. Here, we present evidence that the nuclear exporter exportin-6 and its cargo profilin-1 constitute a functionally important and frequently deregulated axis in cancer. Exportin-6 upregulation occurs in numerous cancer types and is associated with poor patient survival. Reducing exportin-6 level in breast cancer cells triggers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(44 citation statements)
references
References 68 publications
(101 reference statements)
2
42
0
Order By: Relevance
“…Our prior study suggested that some of these anticancer activities may stem from nuclear Pfn1 (Diamond et al, 2015). Our more recent work supported this theory and demonstrated that nuclear Pfn1 functions as a transcriptional repressor by binding and inhibiting the Super Elongation Complex (SEC), a positive regulator of transcriptional elongation of many pro-cancer genes (Zhu et al, 2021). Furthermore, we provided evidence that Pfn1 undergoes spatial deregulation in a broad range of cancer due to overexpression of its nuclear exporter exportin-6.…”
Section: Introductionsupporting
confidence: 59%
See 4 more Smart Citations
“…Our prior study suggested that some of these anticancer activities may stem from nuclear Pfn1 (Diamond et al, 2015). Our more recent work supported this theory and demonstrated that nuclear Pfn1 functions as a transcriptional repressor by binding and inhibiting the Super Elongation Complex (SEC), a positive regulator of transcriptional elongation of many pro-cancer genes (Zhu et al, 2021). Furthermore, we provided evidence that Pfn1 undergoes spatial deregulation in a broad range of cancer due to overexpression of its nuclear exporter exportin-6.…”
Section: Introductionsupporting
confidence: 59%
“…Untagged, Myc-tagged, and HA-tagged Pfn1 in pcDNA3, His-tagged Pfn1 in pRK172, untagged Pfn1 in pLenti-CMV/TO-Neo-DEST, and YFP-Pfn1 with and without NES or NLS tag in pFLRu-FH vector have been described previously ( Shao et al, 2008b ; Diamond et al, 2015 ; Zhu et al, 2021 ). Point mutations (S71A and S71D) within Pfn1 were introduced by site-directed mutagenesis using QuikChange.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations